Compact TiO2 blocking-layer prepared by LbL for perovskite solar cells. (15th January 2021) - Veiga, Elaine Teixeira; Fernandes, Silvia Letícia; Graeff, Carlos Frederico de Oliveira; Polo, André Sarto
Highlights: Compact layers for perovskite solar cells were prepared by Layer-by-Layer technique. Layer-by-Layer compact layers can be prepared with a fine adjust of their thickness. The compact-layer thickness affects directly the efficiency of PSCs. Abstract: Blocking-layer are very important for the overall efficiency improvement in perovskite solar cells, PSCs. This layer must be thin enough to allow the light to reach the perovskite layer and have low electrical resistance for electron flow to the external circuit and, at the same time, inhibit recombination processes on the FTO surface. In this work, the preparation of the TiO2 compact layer by the Layer-by-Layer technique for the use in PSCs is presented. Evaluation of layers having different thickness by several techniques demonstrated that these layers have an optimum thickness and a balance between their electrical resistance and electron recombination is responsible for the improvement in the performance of the cells.